WHO International Health Regulations (IHR) vs COVID-19 Uncertainty - Stuckelberger, Astrid; Urbina, Manuel (Acta Biomedica Atenei Parmensis, 2020)
One of WHO primary function is to control and monitor internationally the spread of infectious diseases of the common killers. After SARS-COV, the International Health Regulations (IHR) was adopted in 2005 by all 194 member states to set up national preparedness for an efficient “early alert and response system”. COVID-19 is a novel virus with an unpredictable course and many uncertainties about its biological, clinical and epidemiological characteristics. COVID-19 is a game changer and calls for a revision of IHR as well as a more biological, clinical and community-cantered preparedness strategy.